Exploring Experiential Metafunction of They Have Cut Down the Pines by Marry Lisle - Zohaib ur Rehman; Zumer Rubab; Sadiq Khan (Indus Journal of Social Sciences, 2025)
The study investigates “They Have Cut Down the Pines” by Marry Lisle employing Transitivity Analysis proposed by M.A.K Halliday (1980). Basing on the mixed-method approach, this study undertakes “Toward an Eco-pedagogy of Children’s Environmental Literature” a theory proposed by Greta Gaard (2008). Carrying clause as a basic unit of meaning, the scholar has initially split the text into fifteen clauses to bring out the bottom line meaning of its own. For the scholar has decontextualized overall experiential metafunction implied through the patterns of mental, material, existential and relational attributive processes. In order to attempt on the text, the scholar adopts close reading technique and purposive sampling as part of method. After unveiling deep inside ideology of preserving nature, the scholar, at the end, for future scholars, has given significant gaps to be explored by applying M.A.K. Halliday’s (1994) approach on the similar text.